Integrated Physical-Digital Workflow in Prototyping – Inspirations from the Digital Twin. (May 2022) - Snider, C.; Kent, L.; Goudswaard, M.; Hicks, B.
Abstract: Prototyping uses many models over its process, with varying strength and weakness offered by those in the physical vs digital domains. Working across domains is necessary but introduces a transition cost, process complexities, and risks lost learning. Drawing from Digital Twinning, this work explores the creation of integrated physical-digital prototyping workflows, where technology enables simultaneous cross-domain working. It contrasts four case-study implementations of integrated prototyping workflow to current practice, exploring feasibility, value, and implementation challenges.